Determination of Copper, Manganese, Nickel and Zinc in Different Cigarette Brands Available in Pakistan: Determination of Metals in Different Cigarettes - Hashmi, Durdana Rais; Siddiqui, Ishratullah; Khan, Farooq Ahmad; Shareef, Akhtar; Shaikh, Ghulam Hussain; Munshi, Alia Bano (Biological Sciences - PJSIR, 2009)
Mean values of copper, manganese, nickel and zinc in different cigarette brands sold in Pakistan were found to be in the range of 8.61 to 94.67 ?g/g, 26.40 to 98.20 mg/g, 0.61 to 8.58 mg/g and 16.92 to 99.60 mg/g, respectively, through Atomic Absorption Spectrophotometer (AAS). The results are discussed with reference to and in comparison with the mean average concentration of these elements reported in the cigarettes of other countries.